Synthesis of bio-polyol through continuous hydroxylation of epoxidized palm oleic acid / Intan Suhada Azmi - Azmi, Intan Suhada (2023)
The world’s consumption of raw materials has shifted from the use of non-renewable materials to renewable materials. Studies on greener epoxidation by using vegetable oils to produce eco-friendly polyol have also increased. Polyols are polymers that contain hydroxyl groups in their structure. They have a relevant commercial value as building blocks, intermediates in organic synthesis, or precursors for production of polyurethane. Epoxidation and hydroxylation are the most widely used methods for the synthesis of polyol because of their low cost and lower environmental impact. However, in previous studies, the typical palm-based polyol produced by this method had low hydroxyl values of less than 200 mg KOH/g, limiting its application in certain polymer formulations such as rigid polyurethane foams. The low hydroxyl values are due to no consideration of oxirane stability, which can provide sufficient time for the alcohol to react with epoxide for the formation of polyols. The aim of this study is to produce a polyol-based epoxidized palm oleic acid (PEPOA) with a high hydroxyl value by a novel method, continuous hydroxylation of epoxidized palm oleic acid (EPOA). Starting from raw palm oleic acid (POA), the double bonds are functionalized by introducing epoxy groups and ring-opened to produce hydroxyl groups. The alcohol (methanol) was used as a ring opening reagent. Epoxidation by in situ peracid mechanism via the used of heterogeneous catalyst (titanium dioxide) was applied in this study. The Taguchi method was applied to optimize the epoxidation process for the synthesis of maximum EPOA in terms of oxirane yield and stability as an intermediate product.